Fungi isolated from food samples for an efficient stereoselective production of phenylethanols. (October 2017) - Decarlini, María F.; Aimar, Mario L.; Vázquez, Ana M.; Vero, Silvana; Rossi, Laura I.; Yang, Pablo
Abstract: Twenty strains of fungi isolated from food samples were screened for the asymmetric reduction of acetophenone. A dimorphic fungus denominated initially as GZ1 and isolated from a carrot sour rot showed very high reduction activities, and based on phenotypic and genetic characteristics was identified as Galactomyces candidus. The only product of the reduction was confirmed to be ( R )-1-phenylethanol. The bioreduction conditions mediated by Gal. candidus GZ1 were investigated, and the optimal conditions in terms of acetophenone concentration, temperature, pH media, co-solvent, the charge of inoculum and shaking speed were established. Under the optimal conditions of 1.875 g/L of acetophenone dissolved in DMSO (1.25% v/v), 112.5 g/L of microorganism cells in 100 mM sterile phosphate buffer solution at pH 7.0, 25 °C and 150 rpm, the conversion and enantiomeric excess values after 48 h reaction were 99% and > 99.9%, respectively. A preparative scale reaction of ( R )-1-phenylethanol was made and the isolated yield was 82% with > 99.9 e.e.%. Additionally, a study using several substituted acetophenones was carried out, and the advantages and scope of GZ1 in the production of chiral 1-phenylethanols were established. In this sense, good results were obtained with 3′-hydroxyacetophenone and a preparative scale reaction was performed which give ( R )-1-(3′-hydroxyphenyl)ethanol (key intermediate of Rivastigmine) with 53% of isolated yield and > 99.9 e.e.%. Highlights: A screening of fungi to reduce acetophenone stereoselectively was made. Galactomyces candidus GZ1 was identified as an efficient bioreductor. Studies for the optimization of the methology were made. Advantage and scope of Gal. candidus GZ1 as bioreductor were stablished. ( R )-1-phenyl- and ( R )-1-(3-hydroxyphenyl)ethanol were obtained in preparative scale.